Nest-site selection of Lepidochelys olivacea (Testudines: Cheloniidae) in the South Pacific region of Costa Rica. - Ávila-Aguilar, Andrés (2015)
In sea turtles, nest-site selection plays a key role in the survival of the offspring, with a direct influence on the sex of the hatchlings, incubation period, embryonic mortality, and hatchling size. Nest-site choice has been studied for most sea turtle species, but the information for Lepidochelys olivacea, the most abundant sea turtle species, is scarce. The present work explores the spatial nesting patterns of L. olivacea and seeks to determine whether this species employs a scatter nesting strategy or chooses to clump its nests based on a specific spatial preference. Night patrols were conducted between July and September 2011 at the beaches of Piro and Pejeperro, located in the Osa Peninsula, in the South Pacific region of Costa Rica. Nest-site location was evaluated by measuring the distance from the tide line to the nest, distance from nest to vegetation, and by noting beach sector according to beach-marker setup. In total, 84 nesting turtles were observed. Sea turtles in both beaches showed a strong preference to locate their nests as far from the tide line as possible, crawling longer distances when presented with wider stretches of beach. Turtles nesting at Piro beach also favored areas that were close to the river mouth, while turtles at Pejeperro preferred to nest near an estuary. It seems that the main driving force that influences L. olivacea to choose a nest site is to protect the eggs from tidal inundation, even if this means a higher predation risk from nesting too close to the vegetation, in addition to a longer trip to the ocean for both the female adult and the hatchlings. Nests near rivers and estuaries may have higher hatching success, which could prompt females to return and select these areas due to imprinting or philopatry. Future research focused on recapture could provide valuable information on individual behavior, and prove whether or not L. olivacea shows strong nest-site fidelity and repeatability of nesting preferences at the individual level.